Microstructural and chemical characterization of radiation-induced carious dentin of teeth submitted to ionizing radiation as a head and neck cancer therapy - Bruna L. Nascimento; Paulo Soares; Rodrigo N. Rached; Paulo H. Couto Souza; Luciana R. A. Alanis; Evelise M. Souza (PLoS ONE, 2025)
Radiation-induced caries is a common side effect of radiotherapy for head and neck cancer caused by pulpal hypovascularization and dentin collagen degradation by the direct action of ionizing radiation. A thorough understanding of radiation-induced changes in dental structure can lead to more effective and durable restorative treatments. The objective of this study was to analyze the microstructure and chemical composition of radiation-induced carious dentin (CD) compared with irradiated (ID) and sound dentin (SD) by using analytical techniques, including scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). Specimens of CD and ID were obtained from patients who had undergone radiotherapy. SD that had not been irradiated was used as a control group. The specimens were sectioned, fixated, and dehydrated according to each type of analysis and equipment. The SEM analysis revealed varying degrees of microstructural degradation in both CD and ID groups. The EDS analysis showed higher levels of carbon in both ID and CD (p < 0.05) and the levels of calcium and phosphorus were significantly higher in SD (p < 0.05). ID and CD demonstrated the absence of the 1-1-2 and 3-0-0 peaks in the XRD analysis and less pronounced carbonate peaks in FTIR. The results are correlated with changes in the composition of the crystalline and collagen structure found in CD and ID. These morphological and chemical changes suggest that radiation might cause a reduction in the quality of hydroxyapatite and collagen degradation, which could negatively affect the effectiveness and decrease the longevity of adhesive restorative treatments of irradiated teeth.